Salmonella spvC Gene Inhibits Autophagy of Host Cells and Suppresses NLRP3 as Well as NLRC4 - Zhou, Liting; Li, Yuanyuan; Gao, Song; Yuan, Haibo; Zuo, Lingli; Wu, Chaoyi; Huang, Rui; Wu, Shuyan (Frontiers in Immunology, 2021)
Salmonella spvC gene, encoding a phosphothreonine lyase on host mitogen-activated protein kinases, facilitates systemic infection of Salmonella while the precise mechanisms remain elusive. Autophagy and pyroptosis dependent on the activation of inflammasomes, as parts of innate immune response, contribute to host defense against Salmonella infection. Recently, we reported that spvC could inhibit pyroptosis. To explore the effect of spvC on autophagy and the relationship between its function in pyroptosis and autophagy, infection models of macrophages J774A.1 and epithelial HeLa cells co-cultured with Salmonella Typhimurium wild type, spvC deletion, site-directed mutant which lacks phosphothreonine lyase activity, or complemented strain were established. The levels of LC3 turnover and Beclin 1 of J774A.1 cells were determined by western blot. Confocal laser scanning microscopy was used to visualize the autophagic flux after being transfected with mRFP-GFP-LC3 plasmid in HeLa cells. Results showed that SpvC inhibited autophagosome formation through its phosphothreonine lyase activity. Additionally, analysis of nucleotide-binding oligomerization domain, leucine-rich repeat and pyrin domain-containing 3 (NLRP3) and NLR with CARD domain-containing 4 (NLRC4) in J774A.1 cells indicated that spvC decreased the protein levels of NLRP3 and NLRC4, which were significantly changed by autophagy inhibitor Bafilomycin A1. Together, our observations reveal a novel mechanism of spvC in Salmonella pathogenesis and host inflammatory response via inhibiting autophagy and NLRP3 as well as NLRC4. These pathways and their subversion by diverse pathogen virulence determinants are expected to throw light on the design of anti-infective agents.